The perception of Obstructive Sleep Apnoea/Hypopnoea Syndrome (OSAHS) among Italian general practitioners - Lombardi, Carlo (Clin Mol Allergy, 2015)
BACKGROUND: Obstructive Sleep Apnoea/Hypopnoea Syndrome (OSAHS) is a common disorder in the general population but often underestimated and underdiagnosed. METHODS: This questionnaire-based study evaluated the overall level of knowledge about OSAHS among Italian General Practitioners (GPs), who are frequently involved in the management of this complex disease. This represents an interesting aspect, because GPs intercept many of the patients with OSAHS, in which C-PAP could be potentially indicated. Randomly-selected GPs were provided with questionnaires, which were then returned anonymously. RESULTS: 80 questionnaires have been validated; the participants in the sample examined were represented by 43 females and 37 males; the average age of participants was 51 years. The general knowledge on OSAHS is overall satisfactory among GPs; it is recognized by most of the GPs interviewed as pathology in constant increase, and associated with predisposing factors such as obesity. High blood pressure is perceived as an independent cardiovascular risk factor in patients with OSAHS, in line with the majority of international studies. The C-PAP has been identified as the care gold standard in patients with OSAHS, despite the lack of patient compliance in relation to this procedure, while polysomnography was found to be the main instrumental procedure used in the diagnostic workup of OSAS. The pulmonologist and a multidisciplinary team have been identified as the specialist figures of reference to which to direct the patient through the diagnostic workup. Respiratory therapists and nurses represent the role of educator in the proper management of the C-PAP in the opinion of 62% of respondents, while only 34% think that this role should be played by the GPs and/or other specialists. CONCLUSIONS: In conclusion, this survey about the perception of OSAHS among GPs in Italy highlighted a satisfactory overall knowledge of OSAHS and only few weak points.